Genome-Wide CRISPR/Cas9 Screening Unveils a Novel Target ATF7IP-SETDB1 Complex for Enhancing Difficult-to-Express Protein Production - Kim, Su Hyun; Park, Jong Ho; Shin, Sungwook; Shin, Seunghyeon; Chun, Dahyun; Kim, Yeon Gu; Yoo, Jiseon; You, Weon Kyoo; Lee, Jae Seong; Lee, Gyun Min (ACS Synthetic Biology, 2024)
With the emerging novel biotherapeutics that are typically difficult-to-express (DTE), improvement is required for high-yield production. To identify novel targets that can enhance DTE protein production, we performed genome-wide fluorescence-activated cell sorting (FACS)-based clustered regularly interspaced short palindromic repeats (CRISPR) knockout screening in bispecific antibody (bsAb)-producing Chinese hamster ovary (CHO) cells. The screen identified the two highest-scoring genes, Atf7ip and Setdb1, which are the binding partners for H3K9me3-mediated transcriptional repression. The ATF7IP-SETDB1 complex knockout in bsAb-producing CHO cells suppressed cell growth but enhanced productivity by up to 2.7-fold. Decreased H3K9me3 levels and an increased transcriptional expression level of the transgene were also observed. Furthermore, perturbation of the ATF7IP-SETDB1 complex in monoclonal antibody (mAb)-producing CHO cells led to substantial improvements in mAb production, increasing the productivity by up to 3.9-fold without affecting the product quality. Taken together, the genome-wide FACS-based CRISPR screen identified promising targets associated with histone methylation, whose perturbation enhanced the productivity by unlocking the transgene expression.
Keywords: Animals; Antibodies, Monoclonal; CHO Cells; Cricetinae; Cricetulus; CRISPR-Cas Systems; Genome; Protein Processing, Post-Translational; Chinese hamster ovary cells; CRISPR/Cas9 screen; difficult-to-express protein; FACS; histone methylation